Pemanfaatan E-Learning Sebagai Inovasi Media Pembelajaran PAI di Era Revolusi Industri 4.0 - Siti Rohmaturrosyidah Ratnawati; Wilis Werdiningsih (Belajea: Jurnal Pendidikan Islam, 2020)
Indonesia has entered a new round of the 4.0 industrial revolution era which is marked by the massive development of digital-based information and communication technology. This needs to be utilized as well as possible to support the process of education and learning, especially Islamic Religious Education (PAI). Moreover, the tendency and interest in learning among millennials today have shifted. By using descriptive qualitative research method, this paper aims to study in depth about the use of e-learning in PAI learning at SMK PGRI 2 Ponorogo as an effort to respond to the presence of the 4.0 industrial revolution era with all the developments and advancements in it. This paper ends at the conclusion that the use of e-learning in PAI learning at SMK PGRI 2 Ponorogo is intended to support learning activities so that it becomes more innovative, interesting, fun, and not monotonous. To bridge concerns about the loss of value inculcating in the application of e-learning, the PAI Teacher of SMK PGRI 2 Ponorogo carried out learning with a blended-learning system, which is a combination of face-to-face and distance learning. As for the implementation phase, PAI teacher at SMK PGRI 2 Ponorogo has carried out important stages related to the implementation of e-learning which include needs analysis, making instructional designs, using and developing e-learning stage, and evaluation